Perancangan animasi: Pentingnya Shalat Jumat untuk ‎meningkatkan inspirasi dalam pemahaman ibadah ‎menggunakan metode pose to pose dengan software ‎blender - Nuraeni, Nenden; Nugroho, Fresy; Karami, Ahmad Fahmi (Maliki Interdisciplinary Journal, 2023)
Animation is an effective visual medium for conveying information in an engaging and easily understandable way. Particularly in the business and education world, animation is used as a popular communication tool to deliver important messages to the audience. This research aims to develop an animation called "Berkah Sholat Jumat" that tells the story of Ali’s life transformation after performing Friday prayers. Through this story, the animation aims to illustrate the importance of Friday prayers and its positive impact on daily life. The research utilizes the "pose to pose" method in the animation process to achieve optimal animation movement quality. The animation production stages involve pre-production, production, and post-production. Blender animation software is used in creating this animation. The expected outcome of this research is an increased understanding and interest among the audience regarding Friday prayers, as well as the potential positive impact it can have on their daily lives. Additionally, it is hoped that this animation can inspire the audience to take Friday prayers seriously and to do good deeds towards others.